Effectiveness of Propioceptive Neuromuscular Facilitation in Improving Walking Quality in Post-Stroke Patients at Haji General Hospital Medan - Liza Agustin; Trisno Susilo (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Nationally, the prevalence of stroke in Indonesia in 2018 was 10.9 per mile, an increase compared to 2013 which was 7 per mile. Stroke is the second leading cause of death and the third leading cause of disability in the world. Two-thirds of stroke events occur in developing countries. Weakness and decreased muscle strength in stroke sufferers occur on one side of the limb, however, in the trunk muscles, weakness occurs on both sides, resulting in limited trunk rotation and difficulty in maintaining balance and gait). Propioceptive Neuromuscular Facilitation (PNF) is a physiotherapy intervention method that can be used to improve the quality of walking in stroke patients. This method can improve proprioceptor function by stimulating it in muscles and tendons. PNF also improves muscle strength, flexibility, and balance). Description of respondent data was carried out using univariate analysis to determine the frequency of age, weight, height, gender, paralyzed side and Wisconsin values ??before and after the intervention for both groups. Bivariate test to compare the average WGS value after treatment with before treatment in both the PNF group and the conventional group and compare the average difference between the PNF group and the conventional group. The average value of the difference before and after the intervention in the PNF group was 1.75 with a standard deviation of ± 0.463, while in the conventional group the average value of the difference before and after the intervention was 0.63 with a standard deviation of ± 0.518. Statistical tests using the Wilcoxon rink test between the two groups obtained a p-value of 0.024, which is smaller than 0.05, which means there is a significant difference between the PNF intervention group and the Conventional intervention group.